The use of Presentation Softwares as an audiovisual resource for an educational activity proposal on “Crash Test” (Research, Society and Development, 2020)
This paper, aims to present a proposal for teaching strength for high school using the potential of  a Presentation Software as an audiovisual resource for creating and editing educational media presentations. The proposal is based on estimating the force exerted on a car in a crash test known as the Crash Test. Using this resource to implement this activity favors the articulation of several educational media, for example, text, videos and other symbols, in the same presentation software. The proposal can stimulate an environment in which the subjects of the teaching and learning process dialogue and externalize concepts during the educational activity and, a priori, enables the discussion of an example close to the student's daily reality, making media technology a means that can to potentialize the construction of knowledge by the student.